Peran ASEAN Children’s Forum dalam Mendorong Pemenuhan Hak Partisipasi Anak di Indonesia - Hastira, Muhammad Fajhriyadi; Abdullah, Nurjannah; Asy’ari, Munjin Syafik; Hastira, Muh Fichriyadi (Jurnal Politica, 2024)
This research examines the process of internalization of norms on the fulfillment of children'sparticipation rights by the ASEAN Children's Forum (ACF) in Indonesia and the role ofACF in promoting the fulfillment of these rights through the National Children's Forum in the2018-2022 period. The background of this research is the significant increase in the fulfillmentof children's participation rights in Indonesia during this period and the strategic position ofACF as the only forum in Southeast Asia that directly engages children in discussions relatedto their rights and protection, potentially influencing policies at the regional and nationallevels. The method used is descriptive qualitative research through interviews and literaturestudies, which aims to describe and analyze phenomena based on empirical data. The resultsshow that the process of internalizing children's participation rights norms through the ACF inIndonesia has reached the stage of internalization, although it is mostly driven by Indonesia'sinitiative and commitment to the Convention on the Rights of the Child. In addition, the roleof ACF is reflected in the implementation of National Children's Forum programs that refer toACF outcomes, although the impact is relatively smaller compared to other ASEAN countries.